An Overview of The Significance and Application of Constructability in Value Engineering (CSID Journal of Infrastructure Development, 2022)
Value Engineering (VE) and constructability are not distinct; instead, they are complementary work processes that may be used as vital elements in achieving total quality. Constructability is a value management (VM) tool developed as an attempt to integrate design and construction activities. VE is often implemented when there is a limited chance to influence the cost and time of the project effectively. Thus, project contractors and owners conduct VE analysis before construction by applying the constructability process. The activities of these two processes somehow complement each other in achieving their goals. Considering the output of existing VE approaches, it seems that despite the significance of constructability, it does not have an appropriate significance in VE projects. This study aims to evaluate the importance of constructability in VE and provide some suggestions for facilitating and improving it with VE.  A type of systematic review in the related literature and conducted pattern coding called overview was utilized to obtain the study's aim. The research found that a large part of the proposed VE solutions that cover the principles and concepts of constructability focused on the pre-study and the main study phases of VE and the management subgroup. Significant areas related to the supplementary studies phase or environmental solutions, including cultural and legal issues, have been neglected. Therefore, addressing them provides an appropriate context to improve constructability by using the VE process.